The Export Performance of Countries within Global Value Chains (GVCs) - Beltramello, Andrea (OECD Science, Technology and Industry Working Papers, 2012)
The growing importance of global value chains (GVCs) in the international organisation of production increasingly challenges the traditional way of measuring countries' export performance and hence international competitiveness. As a result of growing production fragmentation, a country's export bundle nowadays incorporates imports of intermediate goods representing a (large) part of its value. In this case, simply looking at the evolution of exports may misrepresent the international competitive position of a country. This paper discusses the export performance of countries along the value chain by distinguishing upstream activities (i.e. the production of intermediate inputs) and more downstream activities (e.g. the final assembly of products). The empirical analysis first shows how imports of intermediates increasingly determine the export competitiveness of countries in final products. Second, the paper analyses the developments at the intensive and extensive margins of trade and studies how structural changes in terms of geographical and sectoral composition, largely outside the influence of national policies, have contributed to countries' export performance